Post-COVID-19 Era: Navigating Challenges in Online Thesis Guidance for Academic Enrichment - Ahmad Faza; Johan Setiawan; Eunike Endariahna Surbakti; Albert Richard Dammara Alba; Cindy Febriani Santoso; Fidelia Rahmah; Mella Margareta Veronica; Jacintha Cordelie (International Journal of Science, Technology & Management, 2024)
The integration of information technology (IT) in higher education has significantly enhanced academic performance, with a focus on information systems, electronic thesis management, and legal responsibilities outlined in Higher Education Law No. 12 of 2012. This study explores the challenges and opportunities arising from the transition to online thesis guidance, prompted by the post-COVID-19 era, within the Information Systems Program at Multimedia Nusantara University. Utilizing a qualitative case study approach and thematic analysis, the research uncovers challenges in clarity of instructions, guidance note management, and dynamics of relationships with academic mentors, examiners, and the thesis defense committee. As students navigate the intricate landscape of online thesis guidance, the study emphasizes the importance of transparent communication and adaptability. In conclusion, while IT integration enriches academic quality, challenges identified in online thesis guidance serve as guideposts for institutions to refine strategies and enhance communication. This research provides valuable insights for educational institutions, ensuring a seamless and enriching academic experience for students in the evolving landscape of higher education, particularly in the context of online thesis guidance.